Do we recognize child witnesses of domestic violence as victims? - Milosavljević-Đukić Ivana; Ignjatović Tanja (Temida)
The family, as the primary social group, should provide the child with protection, security and love. However, some families can be the source of a child‘s most intense vulnerability. In these families, children may be exposed to different types of violence or may witness domestic violence. Although the Republic of Serbia guarantees the right to a safe family environment with a large number of international and internal legal instruments, numerous professionals in the child protection system still do not recognize child witnesses of domestic violence as victims. Children are not only victims of domestic violence when directly affected, but also as witnesses in all situations when they are exposed to acts of violence that one family member perpetrates on other members. Children are exposed to violence in the family when they directly observe the violence, but also when they hear sounds, blows, and screams from another room, or when they see the consequences of violence against a family member (bruises, injuries) or feel them (sadness, low mood, fear) see the intervention of the police, emergency and social services, or when they hear relatives and people around them retelling acts of violence. Contemporary findings confirm that exposure to domestic violence harms various spheres of child development (immediate or delayed, short-term or long-term). The subject of this paper is representation of the position of children witnesses of domestic violence in family law, through the review of key international and domestic standards (laws and policies), research and practice analysis. The objective of the paper is to emphasize to the professionals working in the child protection system the importance of recognizing children witnesses of domestic violence as victims, for the system to be able to provide the necessary protection, crucial help and support, i.e. conditions for growth and development in a safe environment, and for the children to achieve the rights which belong to them - meaning freedom from all forms of violence which is an obligation the Republic of Serbia took by ratification of international agreements.